Microstructure and corrosion properties of the AISI 904L weld cladding obtained by the electro slag process - João V.S. Matias (Elsevier, 2021)
The AISI 904L steel is a superaustenitic stainless steel, which presents a good combination of properties like high strength, weldability, and good corrosion resistance. Despite its wide use in several industrial segments, the literature reporting the performance of claddings deposited with this alloy to improve the corrosion performance of equipment is limited. Based on this scenario, this work evaluates the microstructure and corrosion properties of the AISI 904L steel weld cladding obtained by the electroslag welding (ESW) deposited on a carbon steel ASTM A516 Grade 70. Single layer cladding was deposited on 50 × 400 × 400 mm steel plates with average welding energy of 11.7 kJ/mm to obtain the minimum thickness required. After welding, metallographic examination and corrosion tests were performed on samples removed at 1 and 3 mm parallel to the fusion line. Metallographic characterization was performed by optical and scanning electron microscopy. Cyclic polarization tests in 3.5% NaCl solution were performed at the same positions as the metallographic examinations. The results showed that the austenitic microstructure presenting a low volume fraction of secondary phases provided suitable corrosion results for all conditions studied. It evidences that single layer weld overlays obtained with the AISI 904L steel deposited by the ESW process may be considered an adequate alternative for overlay welding with reduced thicknesses because good results were observed at only 1.0 mm from the fusion line, and this could represent a significant cost reduction.